Isothermal Evaporation Rate of Deposited Liquid Aerosols and the SARS-CoV-2 Coronavirus Survival - Pavel S. Grinchuk; Katya I. Fisenko; Sergey P. Fisenko; Svetlana M. Danilova-Tretiak (Aerosol and Air Quality Research)
Abstract It is shown that the evaporation rate of a liquid sample with the height is about several millimeters containing the culture of coronavirus affects its survival on a substrate. Possible mechanisms of such influence can be due to the appearance of large, about 140 bar, non-comprehensive capillary pressures and the associated dynamic forces during the movement of the evaporation front in an aerosol with the virus. A simulation of isothermal evaporation of a thin liquid sample based on the Stefan problem was performed. Evaporation time of the same aqueous sample is practically twice shorter for stainless substrate than for plastic one. The comparison of simulation data and recent experiments on the coronavirus survival on various surfaces showed that the rate of isothermal evaporation of aqueous samples, which is higher for heat-conducting materials, correlates well with the lifetime of the coronavirus on these surfaces. Ceteris paribus, the viral culture should die faster on more thermally conductive and thinner substrates, as well as in lower relative humidity environment, which provide a higher evaporation rate.